Morphological Analysis of the Aortic Arch Branching Patterns in Different Populations - A cross-section study - UMAR, MUHAMMAD; NAZ, IRUM; ISHTIAQ, MISBAH; BAIG, NEGARISH ALAM; ANJUM, ABEER (Pakistan Journal of Medical & Health Sciences, 2025)
Background: There is a considerable anatomical variability in the aortic arch branching pattern within the same population and across populations with important clinical and surgical implications. This is important to understand variation in vascular surgeries, endovascular interventions and diagnostic imaging procedures. Aim: To evaluate and classify the morphological patterns of aortic arch branching in a sample of 100 patients of different ethnic background to determine the frequency of common and variant configurations. Methodology: Contrast-enhanced computed tomography (CT) angiograms of 100 patients were utilized in a cross sectional study using contrast enhanced CT angiograms from a tertiary care hospital. People with congenital heart disease or who had had previous vascular surgery were excluded. Standard classifications of branching patterns were used to classify the branching patterns according to the classical three branch pattern, the bovine arch variant, and other less commonly reported types. Results: Of 100 patients, 68% showed the classical branching pattern of the brachiocephalic trunk, left common carotid artery and left subclavian artery. Most common among subjects of African descent, 22% of patients had the bovine arch configuration. 6% had a rare aberrant right subclavian artery, 4% had other atypical branching patterns, such as double aortic arch, or common origin of carotid and subclavian arteries. Conclusion: Significant population related variations of aortic arch branching is highlighted by the study. However, the classical pattern continues to prevail over the field, but there are significant variations such as bovine arch and aberrant right subclavian artery which should be taken into consideration during pre-surgical planning as well as diagnostic evaluation. Future studies on more diverse populations and larger populations will better illuminate the embryological and clinical significance of these patterns.